Preoperative detection of lymph node metastasis in endometrial cancer: The role of 18-FDG PET/CT - Taş, Mustafa; Yavuz, Adem; Dolanbay, Mehmet; Kaya, Eser; Öner, Gökalp; Özçelik, Bülent (Journal of Surgery and Medicine, 2019)
Aim: Fluorine-18 2-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET)/CT imaging technique combines the advantages of localization and functional imaging, and thus has become a preferred method for detection of metastases to the lymph nodes (LN) of patients with endometrial cancer. The aim of this study was to evaluate the efficacy of 18F-FDG PET/CT imaging results in the detection of metastasis of endometrial cancer to lymph nodes. Methods: This is a retrospective cohort study conducted between 2009 and 2015. The study group consisted of females who were admitted to our clinic and diagnosed with endometrial cancer (n=135). We included patients who underwent LN dissection with pre-operative 18F-FDG PET / CT imaging, and evaluated the capability of this method in terms of its effectiveness in determining metastases to the lymph nodes. Assessments and comparisons were performed with gold-standard pathological methods. Results: The 18F-FDG PET/CT method for identification of lymph node metastases had a sensitivity of 76%, a specificity of 80%, a positive predictive value of 46.34% and a negative predictive value of 93.62%. The overall diagnostic accuracy was 79.26%. Conclusion: Our analysis suggests that 18F-FDG PET/CT has a high negative predictive value with regards to lymph node metastasis in endometrial cancer and may be used effectively in evaluating lymph node metastasis in this cohort.